Association between rest-activity rhythm and cognitive function in the elderly: The U.S. National Health and Nutrition Examination Survey, 2011-2014 - Sun, Xinyi; Yu, Weiwei; Wang, Mingsi; Hu, Jun; Li, Yunong (Frontiers in Endocrinology, 2023)
Abstract Background: Circadian rhythm plays an essential role in various physiological and pathological processes related to cognitive function. The rest-activity rhythm (RAR) is one of the most prominent outputs of the circadian system. However, little is known about the relationships between RAR and different domains of cognitive function in older adults. The purpose of this study was to examine the relationships between RAR and various fields of cognitive function in older Americans. Methods: This study included a total of 2090 older adults ≥ 60 years old from the National Health and Nutrition Examination Survey (NHANES) in 2011-2014. RAR parameters were derived from accelerometer recordings. Cognitive function was assessed using the word learning subtest developed by the Consortium to Establish a Registry for Alzheimer's disease (CERAD W-L), the Animal Fluency Test (AFT) and the Digital Symbol Substitution Test (DSST). Linear regression was used to determine the relationships between RAR parameters (IS, IV, RA, L5, M10) and cognitive function scores (CERAD W-L, AFT, DSST). Results: After adjusting for potential confounders, lower IS and M10 were associated with lower CERAD W-L scores (P=0.033 and P=0.002, respectively). Weaker RA and higher L5 were associated with lower AFT scores (P<0.001 and P=0.001, respectively). And lower IS, RA, and higher L5 were associated with lower DSST scores (P=0.019, P<0.001 and P<0.001, respectively). In addition, the results of sensitivity analysis were similar to those of our main analyses. The main correlation results between the RAR indicators and cognitive function were robust. Conclusions: This study suggested that the weakened and/or disrupted RAR was associated with cognitive decline in different domains in Americans over the age of 60.